Enhancement of sound transmission loss of railway frame using ribless panels - Hee-Min Noh (Advances in Mechanical Engineering)
The railway car body is made of aluminium extrusion comprising various rib shapes. The ribs are designed to enhance the stiffness of the car structure. Although the ribs are intended to support large panels of the aluminium extrusion, they can degrade the noise reduction effect owing to multiple resonant vibrations at high frequencies. Therefore, a scientific attempt was made to improve the railway frame by using ribless panels. First, a structural analysis of the original aluminium extrusion was conducted using computer simulation. The simulation results revealed that the ribs of the frames transmitted noise owing to their resonance in the high-frequency range. Therefore, a new railway frame model, named the ribless panel, was developed in this study. Vibration simulations indicated that the ribless panel was effective in reducing noise and vibrations in the high-frequency range. Furthermore, the ribless panel was reinforced with acrylic plastic to reduce the resonant vibrations of the plates. After examining the transmission loss in cross-sectional railway frames, a comparative test of the noise reduction performance was conducted in the reverberation chamber. The results indicated that the reinforced ribless panel improved the transmission loss in the overall high-frequency range. Specifically, 6.7 dB of transmitted noise was reduced using the new panel suggested in this research.